Agency Cost Terhadap Kebijakan Dividen Perusahaan Manufaktur - Mujahidah, Sorayya Qonita; Sudarsono, Rachmat (Jurnal EMT KITA, 2025)
This research examines the impact of Agency Cost on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2022 period. The study investigates variables such as insider ownership, family ownership, institutional ownership, free cash flow (FCF), collateralizable assets, growth, and control variables (Sales and leverage) on the Dividend Payout Ratio (DPR). The findings reveal that most variables significantly influence DPR, except leverage. The results indicate that ownership structures and financial characteristics play critical roles in shaping dividend policies, reflecting efforts to align managerial and shareholder interests. These findings contribute to a better understanding of agency theory and its implications in the Indonesian manufacturing sector during the dynamic post-pandemic recovery period.